Developing a hot-water drill system for the WISSARD project: 1. Basic drill system components and design. Issue 68 (2014) - Rack, Frank R.; Duling, Dennis; Blythe, Daren; Burnett, Justin; Gibson, Dar; Roberts, Graham; Carpenter, Chad; Lemery, Jeff; Fischbein, Steve
Abstract: A new, clean, hot-water drill system (HWDS) was developed by the Science Management Office, University of Nebraska-Lincoln, for use in the Whillans Ice Stream Subglacial Access Research Drilling (WISSARD) project to gain access to Subglacial Lake Whillans beneath ∼800 m of ice in West Antarctica. One primary borehole was drilled into the basal ice environment of Subglacial Lake Whillans during the initial field season in 2012/13. This paper describes the process of designing, fabricating, assembling, shipping, testing, commissioning and traversing the WISSARD HWDS leading up to the first scientific use of the system.